2021
DOI: 10.1021/acs.analchem.1c00242
|View full text |Cite
|
Sign up to set email alerts
|

Model, Simulation, and Experiments on Moving Exchange Boundary via Ligand and Quantum Dots in Chip Electrophoresis

Abstract: Herein, the quench model of the moving exchange boundary (MEB) was first created via a ligand of 5,5′-dithiobis(2nitro-benzoic acid) (DTNB) and group of 3-mercaptopropionic acid (MPA) capped on QDs, and then the recovery model was formed via MPA and 2-nitro-5-thiobenzoic acid (TNB) capped on QDs. The theory on MEB dynamics and width was developed based on the two reversible models, the simulation was conducted for the illumination of MEB, and the protocol was described for the MEB runs. The experiments reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Since 1970, a series of systematic investigations have been performed on the six moving reaction boundaries (MRB), for example, moving neutralization boundary (MNB) [24][25][26][27][28][29], precipitate boundary [24,30,31], chelation boundary [32], and affinity or recognition boundary [33,34] as well as exchange boundary [35]. Especially, the concept of MRB has shown its valuable applications in separation, quantitative analysis, and sample stacking [25].…”
Section: Introductionmentioning
confidence: 99%
“…Since 1970, a series of systematic investigations have been performed on the six moving reaction boundaries (MRB), for example, moving neutralization boundary (MNB) [24][25][26][27][28][29], precipitate boundary [24,30,31], chelation boundary [32], and affinity or recognition boundary [33,34] as well as exchange boundary [35]. Especially, the concept of MRB has shown its valuable applications in separation, quantitative analysis, and sample stacking [25].…”
Section: Introductionmentioning
confidence: 99%
“…Simulation in the EPD process allows us to better understand the electromigration process and determine the optimal deposition conditions without conducting experiments. Many works have explored the simulation of EPD process thus far. These studies have contributed to the understanding of the processes of zone electrophoresis, moving boundary electrophoresis, , isotachophoresis, isoelectric focusing, and isoelectric trapping . However, no specific studies have clearly shown the effect of the electric field on the thin film structure formed through cathodic electrophoretic deposition of f-MWCNTs.…”
Section: Introductionmentioning
confidence: 99%